RAGE: A potential therapeutic target during FGF1 treatment of diabetes‐mediated liver injury. Issue 10 (31st March 2021) - Zheng, Peipei; Tang, Zonghao; Xiong, Jun; Wang, Beini; Xu, Jingyu; Chen, Lulu; Cai, Shufang; Wu, Chengbiao; Ye, Libing; Xu, Ke; Chen, Zimiao; Wu, Yanqing; et al.
Abstract: As a serious metabolic disease, diabetes causes series of complications that seriously endanger human health. The liver is a key organ for metabolizing glucose and lipids, which substantially contributes to the development of insulin resistance and type 2 diabetes mellitus (T2DM). Exogenous fibroblast growth factor 1 (FGF1) has a great potential for the treatment of diabetes. Receptor of advanced glycation end products (RAGE) is a receptor for advanced glycation end products that involved in the development of diabetes‐triggered complications. Previous study has demonstrated that FGF1 significantly ameliorates diabetes‐mediated liver damage (DMLD). However, whether RAGE is involved in this process is still unknown. In this study, we intraperitoneally injected db/db mice with 0.5 mg/kg FGF1. We confirmed that FGF1 treatment not only significantly ameliorates diabetes‐induced elevated apoptosis in the liver, but also attenuates diabetes‐induced inflammation, then contributes to ameliorate liver dysfunction. Moreover, we found that diabetes triggers the elevated RAGE in hepatocytes, and FGF1 treatment blocks it, suggesting that RAGE may be a key target during FGF1 treatment of diabetes‐induced liver injury. Thus, we further confirmed the role of RAGE in FGF1 treatment of AML12 cells under high glucose condition. We found that D‐ribose, a RAGE agonist, reverses the protective role of FGF1 in AML12 cells. These findings suggest that FGF1 ameliorates diabetes‐induced hepatocyte apoptosis and elevated inflammation via suppressing RAGE pathway. These results suggest that RAGE may be a potential therapeutic target for the treatment of DMLD.